Examining the Level of Interleukin-1 (IL-1) Production by Blood Mononuclear Cells During Treatment of Hyperplastic Skin Deteriorations - Tsepkolenko, V. A. (Problems of Cryobiology and Cryomedicine, 2005)
The production level of interleukin-1 (IL-1) by blood mononuclear cells was significantly increased (by 3.8 times) in blood of patients with cosmetic hyperplastic skin deteriorations if compared with those of the control group. Administration of cryopreserved placenta tissue (CPT) as a part of combined treatment was accompanied with a considerable reduction of IL-1 production and clinical manifestations of the disease. These changes were more pronounced if compared with those for cosmetic skin deteriorations which were traditionally treated.